Comparative analysis and model development of working conditions and sociopsychological factors influencing job satisfaction among office workers - Chae, Uri; Lee, Gihyun; Kang, Austin; Lee, Jooyeoun; Ahn, Dohyun (Journal of Infrastructure, Policy and Development, 2024)
This study aimed to examine the impact of working conditions and sociopsychological factors on job satisfaction among office workers. Using data from the 2017–2018 Working Conditions Survey, exploring how workplace conditions and sociopsychological elements could impact job satisfaction. This study examined data from 9801 workers to explore the effects of working conditions and psychosocial environments on job enthusiasm, which subsequently impacts job satisfaction. Analyzing 1416 office workers, it found that fewer working hours, better work-life balance, improved work conditions, and lower depression levels enhance job enthusiasm, significantly affecting job satisfaction. The work environment had the most substantial impact, encompassing relationships with colleagues, task completion time, and confidence. Work-life imbalance and depression were also significant, with work-life balance being crucial for modern society, especially the younger generation. Poor working conditions and unstable psychosocial environments negatively affect job enthusiasm and satisfaction, with findings supporting previous research on job stress and turnover intentions in various industries. This study highlights the need for organizational policies that support these aspects to improve overall employee well-being and productivity.
Keywords: job enthusiasm; job satisfaction; office work environment; pathway analysis; sociopsychological factors; work-life balance